Rearrangement of a common cellular DNA domain on chromosome 4 in human primary liver tumors. - Pasquinelli, C (1988)
Hepatitis B virus (HBV) DNA integration has been shown to occur frequently in human hepatocellular carcinomas. We have investigated whether common cellular DNA domains might be rearranged, possibly by HBV integration, in human primary liver tumors. Unique cellular DNA sequences adjacent to an HBV integration site were isolated from a patient with hepatitis B surface antigen-positive hepatocellular carcinoma. These probes detected rearrangement of this cellular region of chromosomal DNA in 3 of 50 additional primary liver tumors studied. Of these three tumor samples, two contained HBV DNA, without an apparent link between the viral DNA and the rearranged allele; HBV DNA sequences were not detected in the third tumor sample. By use of a panel of somatic cell hybrids, these unique cellular DNA sequences were shown to be located on chromosome 4. Therefore, this region of chromosomal DNA might be implicated in the formation of different tumors at one step of liver cell transformation, possibly related to HBV integration.